Autonomous Synthesis of Fluorescent Silica Biodots Using Engineered Fusion Proteins - Olmez, Tolga T.; Yuca, Esra; Eyupoglu, Erol; Catalak, Hazal B.; Sahin, Ozgur; Seker, Urartu Ozgur Safak (AMER CHEMICAL SOC, 2018)
Formation of biological materials is a well-controlled process that is orchestrated by biomolecules such as proteins. Proteins can control the nucleation and mineralization of biomaterials, thereby forming the hard tissues of biological organisms, such as bones, teeth, and shells. In this study, the design and implementation of multifunctional designer proteins are demonstrated for fluorescent silica micro/nanoparticle synthesis. The R5 motif of silaffin polypeptide, which is known for its silicification capability, was fused genetically into three spectrally distinct fluorescent proteins with the intention of forming modified fluorescent proteins. The bifunctional R5 peptide domain served as a tag to provide silica synthesis at ambient conditions. Three functional fusion constructs have been prepared, including GFPmut3-R5, Venus YFP-R5, and mCherry-R5. Recombinant fluorescent proteins were purified using silica-binding peptide tag through silica gel resin. Purified proteins were tested for their binding affinity to silica using quartz crystal microbalance with dissipation monitoring to make sure they can interact strong enough with the silica surfaces. Later, engineered fluorescent proteins were used to synthesize silica nano/microparticles using silica precursor materials. Synthesized silica particles were investigated for their fluorescence properties, including time-resolved fluorescence. Additionally, elemental analysis of the particles was carried out using electron energy loss spectroscopy and energy-filtered transmission electron microscopy. Last, they were tested for their biocompatibility. In this study, we aimed to provide a biomimetic route to synthesize fluorescent silica nanoparticles. Recombinant fluorescent proteins-directed silica nanoparticles synthesis offers a one-step, reliable method to produce fluorescent particles both for biomaterial applications and other nanotechnology applications.
Keywords: RECOMBINANT PROTEINS; BIOMINERALIZATION PROCESSES; AFFINITY PURIFICATION; ENZYME IMMOBILIZATION; GENE-EXPRESSION; IN-VITRO; SI-TAG; NANOPARTICLES; AGGREGATION; PARTICLES; Chemistry